A review of the genus Spiropagurus Stimpson, 1858 (Crustacea: Decapoda: Paguridae) from the China seas - Han, Yuan-Yuan; An, Jian-Mei; Sha, Zhong-Li (Zootaxa, 2016)
Three species of the genus Spiropagurus Stimpson, 1858, are reported in the present paper, including a new species, S. monospinosus sp. nov. This new species is easily recognized by the carpus of the cheliped bearing only one row of spines, whereas two rows are present in the other two species from the China seas. A key to all the species of Spiropagurus is provided.